The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1007/s10029-021-02557-8
|View full text |Cite
|
Sign up to set email alerts
|

Short-term outcomes of minimally invasive retromuscular ventral hernia repair using an enhanced view totally extraperitoneal (eTEP) approach: systematic review and meta-analysis

Abstract: Background The enhanced view totally extraperitoneal (eTEP) approach is becoming increasingly more widely accepted as a promising technique in the treatment of ventral hernia. However, evidence is still lacking regarding the perioperative, postoperative and long-term outcomes of this technique. The aim of this meta-analysis is to summarize the current available evidence regarding the perioperative and short-term outcomes of ventral hernia repair using eTEP. Study design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Our study’s 3-year follow-up demonstrated a low recurrence rate of 2.97%, comparable to other MIS retromuscular repairs described by Aliseda et al [ 40 ] We noted that hernia recurrence showed no significant dependence on mesh type. Instead, recurrence rates were related to surgical technique rather than mesh selection.…”
Section: Discussionsupporting
confidence: 88%
“…Our study’s 3-year follow-up demonstrated a low recurrence rate of 2.97%, comparable to other MIS retromuscular repairs described by Aliseda et al [ 40 ] We noted that hernia recurrence showed no significant dependence on mesh type. Instead, recurrence rates were related to surgical technique rather than mesh selection.…”
Section: Discussionsupporting
confidence: 88%
“…Our study's 3-year follow-up demonstrated a low recurrence rate of 2.97%, comparable to other MIS retromuscular repairs described by Aliseda et al [40] We noted that hernia recurrence showed no significant dependence on mesh type. Instead, recurrence rates were related to surgical technique rather than mesh selection.…”
Section: Discussionsupporting
confidence: 88%
“…Sin embargo, aparecen las complicaciones relacionadas con la colocación de la malla en posición intraperitoneal (IPOM o IPOM-plus), como las adherencias de asas intestinales a la malla y las fístulas (13,14). Además, se sabe que la fijación de la malla durante la reparación tipo IPOM o IPOM plus mediante la utilización de tackers produce altos niveles de dolor postoperatorio y, a veces, dolor crónico que requiere cirugía adicional para la extracción de estos (15).…”
Section: Palavras-chaveunclassified